Adolescent Caffeine Consumption and Aggressive Behavior: A Longitudinal Assessment. Issue 4 (October 2021) - Kristjansson, Alfgeir L.; Kogan, Steven M.; James, Jack E.; Sigfusdottir, Inga Dora
Background: Adolescent caffeine consumption has been linked to aggressive behaviors, although no longitudinal tests have been reported to date. The purpose of this study was to test the longitudinal relations between daily adolescent caffeine consumption and aggressive behaviors. Methods: Two waves of survey data collected 12 months apart in the spring of 2018 and 2019, from the 2004 birth cohort in the Icelandic LIFECOURSE study, were analyzed using structural equation modeling ( N  = 2, 278). Both direct and mediated models were employed. Results: Caffeine use at time 1 (T1) was associated with aggressive behavior at time 2 (T2) ( β = .12, p < .001) independent of aggressive behavior at T1. A considerable added relation was observed between caffeine at T1 and aggressive behavior at T2 via indirect (i.e., mediated) effects of aggressive behavior at T1 (standardized β = .20, p < .001). Over 64% of the standardized total effect ( β = .31) observed between caffeine at T1 and aggressive behavior at T2 was due to mediation. Conclusion: Adolescent caffeine consumption forecasts aggressive behaviors. Caffeine use at T1 increased the likelihood of self-reported aggressive behaviors 12 months later irrespective of level of reported aggressive behavior at T1 while controlling for common confounders.